The Effect of Work Climate and Job Satisfaction on Teachers' Work Motivation at Public Junior High Schools in Komda Tayu, Pati Regency, Indonesia - Teguh Suroso; Ahmad Haryadi; Gunawan Setiadi (Elicit Journal of Education Studies, 2026)
Purpose: This study examines the effects of work climate and job satisfaction on teachers' work motivation among civil servant teachers in public junior high schools in Komda Tayu, Pati Regency, Indonesia, testing their simultaneous contribution within a single structural model. Methodology: A quantitative, cross-sectional design was used. Data were collected from 100 civil servant teachers, selected via proportional random sampling from a population of 134, using a validated Likert-scale questionnaire, and analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 4, with bootstrapping of 5,000 resamples. Results: The measurement model showed strong reliability and validity (AVE ≥ 0.731; CR ≥ 0.956). Work climate had a large, significant positive effect on work motivation (β = 0.792, t = 7.315, p < .001, f² = 4.098), while job satisfaction showed a small, non-significant effect (β = 0.168, t = 0.872, p = .384). Together, both predictors explained 90.5% of the variance in motivation (R² = 0.905; SRMR = 0.069). Novelty and Contribution: This study offers one of the few structural tests jointly examining work climate and job satisfaction as predictors of teacher motivation in a previously unstudied local context, showing that organisational climate substantially outweighs individual satisfaction in predicting motivation among Indonesian public-school civil servant teachers. Practical and Social Implications: Findings suggest school leaders and policymakers should prioritise cultivating a supportive organisational climate over satisfaction-based